Análisis de proceso de baja de activos fijos en el Gobierno Autónomo Descentralizado Municipal del cantón Baba en el periodo 2019-2020 - Bajaña Arizaga, Juley Michael (2021)
The process of derecognition of fixed assets within a public sector entity is carried out when the asset is depreciated in its entirety, due to obsolescence, partial or total loss, theft, purchase endowment or outdated. When the long-lasting good becomes useless it must disappear from the records. Within the decentralized autonomous government of the Baba canton, having fixed assets in good condition is important since a good administration of assets optimizes economic resources in order to provide a better service to its population. The objective of this case study is to analyze the respective treatment carried out by the study entity when completely derecognizing its fixed assets according to its policies and procedures. The research method to be used is inductive, which consists of the particular analysis of the problems detected through the information provided, and the consequence they entail in internal control. In addition, an interview was carried out with the director of the financial department where it was possible to identify the shortcomings that the entity has in relation to regulations and the method of asset derecognition, since the entity has not carried out the procedure for the derecognition of long-term assets, since seven years ago, moreover, they have not had an internal control that proposes guidelines to be followed.